EFEKTIFITAS LAMA PENIRISAN STEK DI MEDIA TANAH BERPASIR TERHADAP PERTUMBUHANKAMBOJA (Adenium obesum) - Saijo (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2012)
The study aims to assess the effectiveness of a long draining cuttings in sandy soil media on the growth of frangipani cuttings (Adenium obesum). The results showed: Cuttings drained to increase as emerging shoots, number of shoots, number of leaves, number of roots and root length. Cuttings drained 8 hours tend to be significantly stimulated the growth of root cuttings Adenium on sandy soil media.Keywords: Draining, adenium, sandy soil media.